Petrol Fuel Station Safety and Risk Assessment Framework - AHMED, M. M (2011)
Petrol Fuel Stations (PFS) are hazardous work places. They store and sell flammable material(petrol, diesel and CNG). Arrival and departure of various kinds of vehicles to take fuel is normal round the clock. Due to availability of flammable materials at PFS poses constant hazard to the staff, public, assets and environment. Minor mistake has the potential to create disastrous situations. Human behavior found one of the dominant factors to create hazard contributing scenarios at PFS. One year data collected (2008) and 1203 events recorded. Other factors related to process failure also exist but requires less attention. 1203 hazard contributing factors further divided into 8 main categories. These are housekeeping (55), transportation hazard (255), slips trips and falls (215), carelessness (244), fire (17), electrical fault (97), medical treatment cases (61) and miscellaneous cases (279). Detail description of these hazards contributing factors also presenting in this paper. Based upon occurrences of these hazard contributing factors, safety and risk assessment framework prepared and is presenting in this study for further implementation.